2019
DOI: 10.1186/s12936-019-2833-8
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic malaria infections and Pfmdr1 mutations in an endemic area of Nigeria

Abstract: Background Malaria eradication globally is yet to be achieved and transmission is sustained in many endemic countries. Plasmodium falciparum continues to develop resistance to currently available anti-malarial drugs, posing great problems for malaria elimination. This study evaluates the frequencies of asymptomatic infection and multidrug resistance-1 ( mdr-1 ) gene mutations in parasite isolates, which form the basis for understanding persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…A diagnosis of cerebral malaria is contingent on the demonstration of asexual forms of P. falciparum in blood smears and the exclusion of alternative causes of a febrile coma. As asymptomatic peripheral blood parasitaemia is well known in SSA on account of immunity, the mere demonstration of the parasite in blood smears might not be sufficient to establish diagnosis 34 . An autopsy study from Malawi showed that seven of 31 children with clinically diagnosed cerebral malaria died from other causes 35 .…”
Section: [H2] Epidemiologymentioning
confidence: 99%
“…A diagnosis of cerebral malaria is contingent on the demonstration of asexual forms of P. falciparum in blood smears and the exclusion of alternative causes of a febrile coma. As asymptomatic peripheral blood parasitaemia is well known in SSA on account of immunity, the mere demonstration of the parasite in blood smears might not be sufficient to establish diagnosis 34 . An autopsy study from Malawi showed that seven of 31 children with clinically diagnosed cerebral malaria died from other causes 35 .…”
Section: [H2] Epidemiologymentioning
confidence: 99%
“…In this study, the D1246Y mutation was not investigated since it is known to be present in approximately only 0.7–3% of the African isolates [ 10 , 30 , 31 ]. However, two studies have recorded 1246Y frequencies of 3.66 and 18.6%, respectively, in southeast and southwest Nigeria [ 24 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the D1246Y mutation was not investigated since it is known to be present in approximately only 0.7–3% of the African isolates [ 10 , 30 , 31 ]. However, two studies have recorded 1246Y frequencies of 3.66 and 18.6%, respectively, in southeast and southwest Nigeria [ 24 , 30 ]. A recently published study conducted in Lagos, southwest Nigeria, detected rare pfmdr1 mutations, N504K, N649D, F938Y and S967N, which were previously unreported [ 21 ], suggesting that the proactive surveillance of this gene and the validation of mutations discovered in it are necessary to ameliorate the menace of multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of pfmdr1 polymorphisms in Nigeria was majorly reported from the Southern region, where a positive association between pfmdr1 N86, F184 and D1246 alleles and clinical failure was observed [ 36 ]. In contrast, a prevalence of 62.2% and 69.0% for pfmdr1 86Y and F184 allele, respectively, was also reported from the region [ 37 ] which was recently followed by another survey where the pfmdr1 86Y and 1246Y alleles had prevalence of 24% and 18.6%, respectively [ 38 ]. Yet, there is no valid baseline data involving pfmdr1 SNPs in both North-West and North–East Nigeria since the withdrawal of CQ and adoption of AL in Northern Nigeria.…”
Section: Introductionmentioning
confidence: 99%